Sleep quality in wheelchair basketball players (Research, Society and Development, 2021)
Introduction: Sleep deprivation or restriction reflects on people's quality of life and increased daytime sleepiness. On the other hand, exercise contributes to improving sleep quality. Poor quality sleep is more prevalent in people with spinal cord injury (SCI) than in the population without SCI. Objective: To evaluate sleep quality and sleepiness in Wheelchair Basketball Players (JBCR). Methods: The sample consisted of 11 male volunteers, basketball athletes in a wheelchair, with complete or incomplete SCI from thoracic 5 (T5) to lumbar 1 (L1). The volunteers answered the Pittsburgh Sleep Quality Questionnaire (PSQI) and the translated version of the Epworth Sleepiness Scale was used to assess daytime sleepiness. Descriptive statistics were used to present the data. Results: 8 athletes (72%) have poor sleep quality reaching scores above 5 on the PSQI. Regarding the total sleep time, the results found show a sleep duration or total sleep time (TTS) of 7.5 hours. Sleep efficiency was 84% ​​and 7 athletes (63%) had latency longer than 15 minutes. Conclusion: The JBCR have poor sleep quality, as demonstrated by the PSQI. However, we believe that regular physical exercise may have attenuated the deleterious effects of ML on sleep.